Using chronological order: Picture sequence in students’ ability of EFL on midwifery students at STIK Bina Husada and STIKES Pembina Palembang - Arief Pamuji (Language and Education Journal, 2021)
In mastering the language, especially in writing and speaking, the students often face the problem. One of the causes is there is no appropriate method to be used. The chronological order: picture sequence is one of the good ways to overcome the problem. The objective of this research was to find out the description of the use of chronological order: picture sequence in students’ ability of EFL on midwifery students at STIK Bina Husada and STIKES Pembina Palembang. The research used a descriptive quantitative design. The sample of this research was taken by using totaling sampling technique with 51 midwifery students from STIKES Pembina and STIK Bina Husada. The data were obtained from the writing and speaking test in two meetings. Then the data analysis showed that students' score of writing from both institutions got the lowest score was 60, the highest score was 88, and the average score was 77.33. While speaking score the students got the lowest score was 65, the highest score was 90, and the average score was 78.35. The use of picture sequence guided them on what should they rewrite and speak based on the story. Therefore, this method leads them to more confidence in writing and speaking. From the result showed it can be concluded that most of the students were helped by using this method or way to rewrite and retell the story in the form of written and spoken.